Kewajiban Dan Hak Siswa Dalam Pandangan Imam Az Zarnuji: Studi Kitab Ta’lim Muta’allim - Tri Yugo (Tamadduna: Jurnal Peradaban, 2024)
The book Ta'lim Muta'allim by Imam Az Zarnuji, a respected Islamic scholar, introduces an in-depth view of the relationship between teachers and students and the responsibilities of each party in the educational process. Teachers are people who are responsible for teaching Islamic knowledge and values and they have the right to be respected and appreciated by their students. Students must listen attentively, respect and obey teachers, behave politely inside and outside the study room, and respect their study environment. The literature review method was used to investigate relevant primary sources, including the works of Imam Az Zarnuji and the interpretations of other Islamic scholars. This research explores concepts such as adab (ethics) in learning, students' rights to get a decent education, and teachers' responsibilities in guiding and setting an example. An in-depth analysis of Imam Az Zarnuji's works shows their relevance in the context of modern education. It provides a deeper understanding of the principles of Islamic education that he fought for. This research has the potential to make an important contribution to our understanding of education in the Islamic tradition and its implications in today's context.